Review of Emerging Additive Manufacturing Technologies in 3D Printing of Cementitious Materials in the Construction Industry - Shakor, Pshtiwan; Nejadi, Shami; Paul, Gavin; Malek, Sardar (Frontiers in Built Environment, 2019)
Additive manufacturing is a fabrication technology that is rapidly revolutionising the manufacturing and construction sectors. In this paper, a review of various prototyping technologies for printing cementitious materials and selected 3D printing techniques are presented in detail. Benchmark examples are provided to compare three well-known printing techniques; inkjet printing (binder jetting), selected laser sintering (SLS) and extrusion printing (FDM). A comprehensive search in the literature was conducted to identify various mix designs that could be employed when printing cementitious materials. Aspects of concrete mix design are described, and some new experiments are conducted to analyse the printability of new mixes by the authors. Future research in the area of the rheology of cementitious materials and its relationship with the structural performance of finished concretes are highlighted.